Phil : the rip-roaring (and unauthorized!) biography of golf's most colorful superstar - Shipnuck, Alan, 1973- (Avid Reader Press, 2022)
"Phil Mickelson is one of the most compelling figures in sports. For more than three decades he has been among the best golfers in the world, and his unmatched longevity was exemplified at the 2021 PGA Championship, when Mickelson, on the cusp of turning fifty-one, became the oldest player in history to win a major championship. In this raw, uncensored, and unauthorized biography, Alan Shipnuck captures a singular life defined by thrilling victories, crushing defeats, and countless controversies. Mickelson is a multifaceted character, and all his warring impulses are on display in these pages: He is a smart-ass who built an empire on being the consummate professional; a loving husband dogged by salacious rumors; a high-stakes gambler who knows the house always wins but can't tear himself away. Mickelson's career and public image have been defined by the contrast with his lifelong rival, Tiger Woods. Where Woods is robotic and reticent, Mickelson is affable and extroverted, an incorrigible showman whom many fans love and some abhor because of the overwhelming size of his personality. In their early years together on Tour, Mickelson lacked Tiger's laser focus and discipline, leading Tida Woods to call her son's rival "the fat boy," among other put-downs. Yet as Tiger's career has been curtailed by scandal, addiction, and a broken body, Phil sails on, still relevant on the golf course and in the marketplace" --